Implementation Of Ct-Scan And Mri (Magnetic Resonance Imaging) For Medical Record Data (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
image processing is any form of signal processing where the input is an image such as a photo or video frame. Image acquisition or that produces an input image in the first place is called imaging. This process has the characteristics of input data and output information in the form of images. The term digital image processing is generally defined as two-dimensional image processing by computer. In a broader definition, digital image processing also includes all two-dimensional data. A digital image is a series of real or complex numbers represented by certain bits. In the field of modern medical science, a doctor is able to analyze a patient's disease through a visual image of the results of an internal disease or more modern a doctor can use the CT-SCAN reading technique ( Computed Tomography) which is able to draw visually as well as more modern MRI techniques displaying data in 3 dimensions so that it is more accurate.